2021
DOI: 10.1017/s1092852921000833
|View full text |Cite
|
Sign up to set email alerts
|

When neurologists diagnose functional neurological disorder, why don’t they code for it?

Abstract: Background Clinicians who recognize functional neurological disorders (FND) may not share that diagnosis with patients. Poor communication delays treatment and contributes to substantial disability in FND. Diagnostic (ICD-10) coding, one form of medical communication, offers an insight into clinicians’ face-to-face communication. Therefore, quantifying the phenomenon of noncoding, and identifying beliefs and practice habits that reduce coding, may suggest routes to improve medical communication in FND. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…The number of FMD patients may be underestimated overall and within the EDS patient sample. It has been reported that after making a diagnosis of FND only 22.8% of neurologists code for FND after the consultation 25 . There is also the chance of misdiagnosis of functional versus other movement disorder, which could have skewed our data.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The number of FMD patients may be underestimated overall and within the EDS patient sample. It has been reported that after making a diagnosis of FND only 22.8% of neurologists code for FND after the consultation 25 . There is also the chance of misdiagnosis of functional versus other movement disorder, which could have skewed our data.…”
Section: Discussionmentioning
confidence: 90%
“…It has been reported that after making a diagnosis of FND only 22.8% of neurologists code for FND after the consultation. 25 There is also the chance of misdiagnosis of functional versus other movement disorder, which could have skewed our data. The rate of misdiagnosis of FMD is reportedly low, occurring in 4% of 1466 patients included in a meta-analysis of 27 studies.…”
Section: Discussionmentioning
confidence: 99%
“…All these clinicians and their teams have contributed to recent advances in theory, best-practice guidelines, and evaluation of treatment outcomes, thereby providing direction for clinicians around the world (see Supplemental Text Box 2, http://links.lww.com/HRP/A210). 10,11,15,20,25,37,40,43,58,59,74,80,81,92,108–128 Through collaborative efforts, these teams have also worked hard to highlight that the pressing need to develop an FND-informed culture of care that takes into account recent advances in our understanding and clinical care of children and adolescents with FND 26 …”
Section: Discussionmentioning
confidence: 99%
“…Reduced communication of FND through medical record documentation may be linked to the ongoing confusion or reduced confidence about defining and diagnosing FND. Other potential drivers reported in the literature include doctors still incorrectly treating FND as a diagnosis of exclusion, 30 continuing to fear misdiagnosis, 12 and holding FND to a higher diagnostic threshold than other neurological disorders 31 . There are ethical implications of withholding a diagnosis and limitations to capturing the required services to manage FND.…”
Section: Discussionmentioning
confidence: 99%
“…The key steps in developing these specialized services are improving education of health care professionals and developing targeted clinical pathways 32,37 . These may lead to improved access to coordinated multidisciplinary management and likely subsequently reduce stigma and disability through improving patient outcomes 31,32,37 …”
Section: Discussionmentioning
confidence: 99%